Religio-magicism of Sasak: the Qur’anic Mantras in the Healing Rituals of Lombok Community - Quddus, Abdul (International Journal of Psychosocial Rehabilitation, 2020)
This paper aimed to examine the Qur’anic values living and thriving in the magic tradition of Sasak Lombok (the indigenous ethnic of Lombok). The analysis was done ethnographically using an anthropological approach. Drawing on the cultural analysis, it was to interpret either independent and related phenomena or those constituting other phenomena in the realm of Sasak culture, Lombok. The findings unveiled that the Qur’anic mantras and the cultural values of magicism for the Sasak community were the representation of Karamah (miracles bestowed upon Auliya) and Mu’jizat (miracles adhered to prophets) to gain some benefits, such as medical treatment, salvation, wealth, mate, political position, and even environmental conservation. For Sasak people, the Qur’anic mantras were unique elements of religion and culture adhered not to customary leaders or traditional healers, yet to spiritual experts deemed as religious consultants and medical experts, who were able to compose herbal medicines, and whose ability was inherited directly through the line of descent. The culture of Sasak viewed Qur’anic mantras as central characters in representing the religiosity and spirituality of the Sasak community; hence, the practice of the Qur’anic mantras in the healing rituals of Sasaknese has a unique and sacred position.